2004
DOI: 10.1016/s0014-5793(04)00292-3
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of Na+,K+‐ATPase α3‐isoform and down‐regulation of the α1‐isoform in human colorectal cancer

Abstract: We investigated expression levels of Na + ,K + -ATPase K K-isoforms and their ATPase activities in human colorectal cancer tissue and the accompanying normal mucosa. A decrease in expression of the K K1-isoform protein was observed in all sampled cancer tissues compared with the normal mucosae. The level of ouabain (5 W WM)-sensitive Na + ,K + -ATPase activity in carcinomas was 81 þ 5% that of in the normal mucosae. The mRNA expression of K K2-and K K4-isoforms was decreased in almost all the carcinoma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 17 publications
4
74
0
Order By: Relevance
“…For instance, certain of these same studies also reported no significant change in the expression patterns of α1 isoform associated with lung or renal cancers (21,44), whereas other examples from these same studies reported decreased expression of the α1 isoform in human gastric and bladder cancers (23,24). In the colon, the expression of α1 isoform was decreased in carcinoma compared with normal control samples, whereas the expression of α3 isoform protein was increased in 13 of 17 carcinomas (76%) compared with normal samples (45). Additionally, earlier reports showed that Na,K-ATPase activity was altered in malignant compared with normal cells (46)(47)(48).…”
Section: Discussionmentioning
confidence: 91%
“…For instance, certain of these same studies also reported no significant change in the expression patterns of α1 isoform associated with lung or renal cancers (21,44), whereas other examples from these same studies reported decreased expression of the α1 isoform in human gastric and bladder cancers (23,24). In the colon, the expression of α1 isoform was decreased in carcinoma compared with normal control samples, whereas the expression of α3 isoform protein was increased in 13 of 17 carcinomas (76%) compared with normal samples (45). Additionally, earlier reports showed that Na,K-ATPase activity was altered in malignant compared with normal cells (46)(47)(48).…”
Section: Discussionmentioning
confidence: 91%
“…The activity of other enzymes involved in oxidative phosphorylation is known to be decreased in cancer cells. The alpha subunit of mitochondrial F(1)F(0)-ATP synthase has been shown to be downregulated in colorectal carcinomas (Sakai et al, 2004;Shin et al, 2005). Studies have also revealed reduced expression of the beta 1-subunit of Na-K-ATPase in poorly differentiated carcinoma cell lines derived from colon, breast, kidney and pancreas (Espineda et al, 2004).…”
Section: Other Solid Tumorsmentioning
confidence: 99%
“…Overall, this is the first report to provide systematic evidence that cardiac glycosides at higher doses might induce apoptosis in cancer cells through the same pathways that induce proliferation in nontransformed cells. Increased expression of the sodium pump subunits by cancer cells might account for this differential effect of these drugs between cancer and normal cells (22)(23)(24). Further studies are necessary to fully elucidate the exact involvement of these particular kinases in the molecular mechanism of cardiac glycoside action.…”
Section: Characterization Of Cardiac Glycoside-induced Cell Deathmentioning
confidence: 99%